Methods and applications in reservoir geophysics - Johnston, David H.; Abriel, William L., 1953-; Cooper, Michael R., 1947- (Society of Exploration Geophysicists, 2010)
Geophysics is not simply an exploration tool. The tasks of delineation and characterization at the reservoir scale are applied throughout the life cycle of a field. Reservoir geophysics, once an emerging application, is now mainstream. The title not only demonstrates the value of geophysics in reservoir management but also shows how to apply geophysical technologies more effectively in reservoir studies. The chapter editors have selected more than 40 papers from SEG and other journals and have added 13 new contributions. In the reservoir-engineering tutorial, geophysicists will discover a rich source of information on issues and data that are critically important to the engineer. In the geophysics tutorial, the engineer and the geophysicist will find explanations of the tools and data discussed in the book's case studies. Each chapter then focuses on a different phase of field life: exploration appraisal, development planning, and production optimization. Geophysics is used in each of those stages to help address the critical technical issues and business decisions that the reservoir-management team faces. The case studies demonstrate the processes, methods, and techniques used in reservoir geophysics, not just the results. The last chapter explores the road ahead and emerging technologies that define the future of reservoir geophysics. This book will be valuable for geophysicists, engineers, and all members of the reservoir-management team who want to ensure that the right data are used to maximize reserves, optimize recovery, and contain costs.
Keywords: Petroleum -- Prospecting.; Seismic prospecting.; Oil reservoir engineering.; Petroleum -- Geology.; elektronické knihy; electronic books